An Efficient and Eco-Friendly Solvent-Free Synthesis of β-Acetamido Ketones Using L-Proline As a Green and Reusable Catalyst - Roshani, M.; Allameh, S.; Darkooti, E. (Asian Journal of Chemistry, 2012)
A simple and efficient catalytic protocol for the synthesis of b-acetamido ketones via the one-pot, four component condensation of aryl aldehydes, enolizable aryl ketones, acetyl chloride and acetonitrile using L-proline is reported. The present method offers several advantages such as high yields, short reaction times, recovery and reusability of catalyst and easy workup procedures.